2001
DOI: 10.1128/aac.45.4.1263-1270.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transposons Tn 1696 and Tn 21 and Their Integrons In4 and In2 Have Independent Origins

Abstract: The first 13.6 kb of the mercury and multidrug resistance transposon Tn1696, which includes the class 1 integron In4, has been sequenced. In4 is 8.33 kb long and contains the 5-conserved segment (5-CS) and 2.24 kb of the 3-conserved segment (3-CS) flanking four integrated cassettes. The 3-CS region is followed by one full copy and an adjacent partial copy of the insertion sequence IS6100 flanked, in inverse orientation, by two short segments (123 and 152 bp) from the outer right-hand end of class 1 integrons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
160
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(171 citation statements)
references
References 53 publications
5
160
0
1
Order By: Relevance
“…However, the estimated sizes of the products (3.5 kb, 2.0 kb, and 1.0 kb, respectively) were all about 0.7 kb smaller than predicted for the standard In4-type integron configuration (26), which is present at the right-hand end of In104 in SGI1 (Fig. 1) and SGI1-A to SGI1-J.…”
Section: Resultsmentioning
confidence: 93%
“…However, the estimated sizes of the products (3.5 kb, 2.0 kb, and 1.0 kb, respectively) were all about 0.7 kb smaller than predicted for the standard In4-type integron configuration (26), which is present at the right-hand end of In104 in SGI1 (Fig. 1) and SGI1-A to SGI1-J.…”
Section: Resultsmentioning
confidence: 93%
“…P. putida SP1 possessed a mer operon as a mercury-resistant determinant like most of the other mercury-resistant bacteria, and the mer operon of P. putida SP1 was located on the chromosomal DNA as described in other strains (De et al 2003;Bafana et al 2010). Because multiple resistance genes are often located on mobile genetic elements (Mindlin et al 2001;Partridge et al 2001;Barkay et al 2003) and genes encoding for heavy metal resistance are often linked to antibiotic resistance genes on the same mobile element (Mindlin et al 2002;Barkay et al 2003), the similarity between the mer operon of P. putida SP1 and the mer operon located on Tn5041 suggested that the environmental bacterium P. putida SP1 may have acquired this chromosomal mer operon and other heavy metal or antibiotic resistance determinants through transposable elements that confer resistance to HgCl 2 and a variety of other xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
“…2C). Multiple resistance genes are most often located in mobile genetic elements [2,4,15], able to spread among the bacterial community very rapidly [6,12]. Considering that 62.96% of the Hgresistant bacterial strains harbored large, potentially conjugative plasmids, we were concerned by the potential acquisition of multiple resistances by human pathogens through conjugation with indigenous bacteria.…”
Section: Discussionmentioning
confidence: 99%